An Integrative Pharmacology Based Analysis of Refined Liuweiwuling Against Liver Injury: A Novel Component Combination and Hepaprotective Mechanism - Gao, Yuan; Shi, Wei; Yao, Hongyu; Ai, Yongqiang; Li, Ruisheng; Wang, Zhilei; Liu, Tingting; Dai, Wenzhang; Xiao, Xiaohe; Zhao, Jun; Niu, Ming; Bai, Zhaofang (Frontiers in Pharmacology, 2021)
Liver disease is a major cause of illness and death worldwide. In China, liver diseases, primarily alcoholic and nonalcoholic fatty liver disease, and viral hepatitis, affect approximately 300 million people, resulting in a major impact on the global burden of liver diseases. The use of Liuweiwuling (LWWL), a traditional Chinese medicine formula, approved by the Chinese Food and Drug Administration for decreasing aminotransferase levels induced by different liver diseases. Our previous study indicated a part of the material basis and mechanisms of LWWL in the treatment of hepatic fibrosis. However, knowledge of the materials and molecular mechanisms of LWWL in the treatment of liver diseases remains limited. Using pharmacokinetic and network pharmacology methods, this study demonstrated that the active components of LWWL were involved in the treatment mechanism against liver diseases and exerted anti-apoptosis and anti-inflammatory effects. Furthermore, esculetin, luteolin, schisandrol A, and schisandrol B may play an important role by exerting anti-inflammatory and hepatoprotective effects in vitro. Esculeti and luteolin dose-dependently inhibited H2O2-induced cell apoptosis, and luteolin also inhibited the NF-κB signaling pathway in bone marrow-derived macrophages. Schisantherin A and B inhibited the release of ROS in acetaminophen (APAP)-induced acute liver injury mice in vitro. Moreover, LWWL active ingredients protect against APAP-induced acute liver injury in mice. The four active ingredients may inhibit oxidative stress or inflammation to exert hepatoprotective effect. In conclusion, our results showed that the novel component combination of LWWL can protect against APAP-induced acute liver injury by inhibiting cell apoptosis and exerting anti-inflammatory effects.